Kajian Fetisisme Pada Keris Jawa - Yunita Fitra Andriana (JURNAL RUPA, 2016)
Keris is one of many traditional weapon in Indonesia which is believed has an aesthetic side along with its superstition power. Therefore, keris collector divided into two kinds, there are collectors who collecting keris for its aesthetic elements and there are collectors who collecting keris for its aesthetic and also for its superstition power elements. Nowadays, Indonesian people still believe in existance of keris superstition power. The superstition power believed has higher value than its phisical power, which is makes keris as a valuable things that worth to be worshiped by Indonesian people. The worships that Indonesian people do to keris because of their belief for its superstition power is an anthropological fetishism.